Keefektifan Model Think Talk Write Pada Keterampilan Menulis Pantun Siswa Kelas IV SD Negeri 05 Rambang - Faurenda, Nahdia; Akhbar, M. Taheri; Syaflin, Sylvia Lara (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to: 1) examine the effectiveness of the Think Talk Write model comparedto the conventional model on the Poetry Writing Skills of fourth grade students of SD Negeri 05 Rambang. 2) to test whether there are differences in rhyme writing skills in fourth grade students of SD Negeri 05 Rambang who apply the Think Talk Write model and those who apply the conventional model.The subjects of this study were the fourth grade students of SD Negeri 05 Rambang with 30 students in class IV.A as the experimental class and class IV.B as many as 30 students as the control class. The method used by the researcher is aquasi-experimental method. Data collection techniques using tests and documentation. Data analysis used N-gain test, normality test, homogeneity test, Independent Sample t-test(t-test).Based on the results of the analysis and discussion, this is evidenced by the calculation of the N-gain score test showing that the average N-gain score for the experimental class is 71.7761 or 71% while for the control class it is 36.4412 or 36%. The think talk write model is effective compared to the conventional model in poetry writing skills, while the use of the conventional model is less effective. And the results of the t-test calculation with a significant level (α) of 0.05 and dk = 30 – 1 = 29 it was found that the value of tcount = 305.56, thus it can be concluded that tcountttable or 305.56 2.43 then H0 is rejected Ha be accepted. This means that the hypothesis states that there are differences in the poetry writing skills of fourth grade students of SD Negeri 05 Rambang who apply the think talk write model and those who apply the conventional model proven true.